2001
DOI: 10.1021/ma010495s
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Reaction Conditions on Degree of Branching in Hyperbranched Aliphatic Polyethers from 3-Ethyl-3-(hydroxymethyl)oxetane

Abstract: The cationic ring-opening polymerization of 3-ethyl-3-(hydroxymethyl)oxetane to form hyperbranched polyethers has been studied. The polymerizations have been performed in bulk using sulfonium salt initiators. To produce polymers of different degrees of branching, the reaction conditions (reaction temperature and initiator) have been varied. Polymerizations have also been performed in the presence of a trifunctional core molecule, trimethylolpropane. The conversion of monomer turned out to be the main factor de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
50
0

Year Published

2002
2002
2014
2014

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 73 publications
(55 citation statements)
references
References 25 publications
5
50
0
Order By: Relevance
“…Both types of hydroxyl groups may have different reactivity; thus, the relative contribution of both mechanisms may change during the polymerization. 47 Magnusson and Malmstrom 49 observed that the content of branched units increases with increasing monomer conversion. An increasing contribution of the AM mechanism in the course of the polymerization can be deduced.…”
Section: Anionic Ring-opening Multibranching Polymerizationmentioning
confidence: 99%
See 2 more Smart Citations
“…Both types of hydroxyl groups may have different reactivity; thus, the relative contribution of both mechanisms may change during the polymerization. 47 Magnusson and Malmstrom 49 observed that the content of branched units increases with increasing monomer conversion. An increasing contribution of the AM mechanism in the course of the polymerization can be deduced.…”
Section: Anionic Ring-opening Multibranching Polymerizationmentioning
confidence: 99%
“…The polydispersity was generally slightly lower when a core molecule was used compared with the one-step homopolymerization. 49 Detailed mechanistic investigations led to the conclusion that the polymerization proceeds with participation of both the ACE and the AM mechanism. 81 An interesting finding is that M n does not increase with monomer conversion and that there seems to be an upper limit of achievable molecular weights, regardless of the reaction conditions.…”
Section: Polyglycerolmentioning
confidence: 99%
See 1 more Smart Citation
“…1 Vandenberg et al 2 reported the synthesis of the polyethers by the cationic ring-opening polymerization of 3-ethyl-3-hydroxymethyloxetane (EHO) in the presence of aluminum complexes as cationic initiators. Recently, Hult et al 3 reported the synthesis of hyperbranched polyethers by the cationic ring-opening polymerization of EHO using various cationic initiators. Penczek et al 4 reported that the cationic ring-opening polymerizations of 3,3-bis(hydroxymethyl)oxetane (BHO), and the copolymerization of BHO with EHO were performed to give medium molecular-weight polymers in good yields.…”
mentioning
confidence: 99%
“…2,3 Hyperbranched polymers by cationic ring-opening polymerization of EHO using sulfonium salts as cationic initiators have been reported. [4][5][6][7] Inoue et al performed living anionic polymerization of oxetanes using aluminum porphyrin/Lewis acid as catalyst. 8 The authors have developed useful reactions of oxetanes for synthetic organic chemistry and polymer synthesis.…”
mentioning
confidence: 99%